Synthesis of poly(aniline-co-o-toluidine) coatings and their corrosion-protection performance on low-carbon steel - Pawar, Pritee; Sainkar, S. R.; Patil, P. P. (Journal of Applied Polymer Science, 2007)
Strongly adherent poly(aniline-co-o-toluidine) coatings were synthesized on low-carbon-steel substrates by the electrochemical copolymerization of aniline with o-toluidine with sodium tartrate as the supporting electrolyte. These coatings were characterized with cyclic voltammetry, ultraviolet-visible absorption spectroscopy, Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, and scanning electron microscopy. The formation of the copolymer with the mixture of monomers in the aqueous sodium tartrate solution was ascertained by a critical comparison of the results obtained from the polymerizations of the individual monomers, aniline and o-toluidine. The optical absorption spectrum of the copolymer was drastically different from the spectra of the respective homopolymers, polyaniline and poly(o-toluidine). The extent of the corrosion protection offered by poly(aniline-co-o-toluidine) coatings to low-carbon steel was investigated in aqueous 3% NaCl solutions by open-circuit-potential measurements and a potentiodynamic polarization technique. The results of the potentiodynamic polarization measurements showed that the poly(aniline-co-o-toluidine) coatings provided more effective corrosion protection to low-carbon steel than the respective homo-polymers. The corrosion rate depended on the feed ratio of o-toluidine used for the synthesis of the copolymer coatings. (c) 2006 Wiley Periodicals, Inc.
Keywords: Coatings; conducting polymers; copolymerization; synthesis